2020
DOI: 10.1186/s12887-020-1935-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with intestinal parasites among children of age 6 to 59 months in, Boricha district, South Ethiopia, in 2018

Abstract: Background: Intestinal parasites are the commonest cause of childhood diarrhea and malnutrition in Ethiopia. Information about intestinal parasites is the first fundamental step for designing intervention strategies against them. Hence, health planners can maximize their efforts. Information is scarce about intestinal parasites among children of under-five years of age in Boricha district. Therefore, this study aimed at assessing prevalence and factors associated with intestinal parasites among children of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 17 publications
4
18
2
Order By: Relevance
“…Mixed infection/polyparasitism was detected, and this agrees with the work of many researchers [3,17,23,30]. Multiple intestinal infections in children have been confirmed to be a natural occurrence triggered by the interaction of common environmental factors, modes of infection, host exposure, vulnerability, as well as behavioural and socioeconomic factors that promote the co-occurrence of various parasites [24]. Gender was not found to be a significant risk factor, both sexes were equally exposed P>0.05.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Mixed infection/polyparasitism was detected, and this agrees with the work of many researchers [3,17,23,30]. Multiple intestinal infections in children have been confirmed to be a natural occurrence triggered by the interaction of common environmental factors, modes of infection, host exposure, vulnerability, as well as behavioural and socioeconomic factors that promote the co-occurrence of various parasites [24]. Gender was not found to be a significant risk factor, both sexes were equally exposed P>0.05.…”
Section: Discussionsupporting
confidence: 89%
“…This high prevalence may due to ignorance, lack of basic amenities, poor sanitation, poverty, inadequate access to healthcare [23]. Differences may also be due to variations in parasitological techniques, source of drinking water, family education, and personal hygiene [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 6.6% of all patients had clinically significant parasite species (excluding B hominis, D fragilis , and E dispar , given their lower risk for causing symptoms/complications): 2.3% had clinically significant protozoans and 4.2% had helminths on stool analysis. The prevalence of intestinal parasites found in our study is much lower than reported in many patients’ countries of birth and origin [ 6 , 36 , 37 ]. Various factors may contribute to these differences, including the natural history of many intestinal parasites clearing with time without intervention.…”
Section: Discussioncontrasting
confidence: 85%
“…The prevalence of clinically significant protozoans was also higher in patients who were born in South Asia, Latin America & the Caribbean, and Middle East & North Africa. Although protozoan infections are endemic in many parts of sub-Sarahan Africa [ 36 , 44 ], we found a relatively low prevalence (0.9%) of clinically significant protozoans in patients from this region.…”
Section: Discussionmentioning
confidence: 52%